EFEKTIVITAS PENGELOLAAN BADAN USAHA MILIK DESA DALAM MENINGKATKAN PENDAPATAN ASLI DESA SIDOMOYO KECAMATAN GODEAN, D.I YOGYAKARTA - Mia Hardiani; Muhamad Rifandi (Politeknik Negeri Ambon, 2023)
The existence of Sidomoyo Makmur village business unit gives economy contribution playing roles in improving economy condition of the village members of society. BUMDes is one of village units which works in economy, social, and culture which plays roles as society aspiration centre and is used in planning development. BUMDes has many names such as in Sidomoyo which is called BUMKal or BUMDes; village land in the form of field and village land located around the field which is made as circuit. Therefore, BUMKal or BUMDes with all their potentials are expected to be empowered in order to improve society prosperity and Original Local Government Revenue in Sidomoyo village. The study aims at analyzing the effectiveness of BUMDes management in improving Original Local Government Revenue of Sidomoyo village of Sidomoyo Godean Sleman DIY. The study used qualitative method and the data collecting technique was through interview and observation. The result of the study showed that the main objective of BUMDes namely improving Original Local Government Revenue is still not effective yet because the profit of Original Local Government Revenue contributed to PADes is not maximum yet. However, the management planning of BUMDes is good. Keywords: Effectiveness, BUMDes management, PADes.